"This Was Being Done Only to Help": Development and Forced Labor in Barue, Mozambique, 1959–1965*. (10th November 2017) - Kagan Guthrie, Zachary
Abstract: This article examines the history of development and forced labor in Barue, a rural district in central Mozambique, in the late 1950s and early 1960s. Throughout the 1940s and 1950s, Barue was designated as a labor reserve, whose economic role was to send forced workers into migrant labor elsewhere. This was slated to change in the early 1960s, with the rise of a new developmental discourse in the Portuguese empire. This discourse promised to transform the economic model of Barue and other rural districts, by outlawing forced labor, minimizing migrant labor, and promoting rural agriculture. The Portuguese government, however, lacked the resources and the commitment necessary to actually change Barue's economy. Instead of development transforming Barue's economic model, the economic model transformed development, which was redefined as a series of modest social and economic improvements which neither changed Barue's economy nor reduced its dependence upon migrant labor. Nonetheless, while this narrower definition of "development" did not fulfill the transformative promise of its discursive progenitor, it was compatible with development's broader objective of defending and justifying the Portuguese empire against the threat of decolonization. The ultimate goal of safeguarding Portuguese rule made it possible to reconcile a discourse founded on change with a reality marked by continuity.